Rare Course of Bilateral Congenital Diaphragmatic Hernia Treated Thoracoscopically—Case Report - Toczewski, Krystian; Gerus, Sylwester; Palczewski, Mateusz; Patkowski, Dariusz (Frontiers in Pediatrics, 2020)
We present a rare case of metachronous bilateral congenital diaphragmatic hernia (CDH) in a newborn with additional malformations: macroglossia, pectus excavatum and confirmed Simpson-Golabi-Behmel syndrome. We performed a successful thoracoscopic subsequent repair with a patch of the bilateral type C CDH. Despite using insufflation that should cause bilateral pneumothorax at first procedure there was no clinical signs of such a one. Contralateral CDH diagnosis was possible only on the basis of the symptoms that occurred after the first operation. After 13 months the patient is without recurrence. In selected patients, staged thoracoscopy may be a safe and feasible method of bilateral CDH treatment.